Pelaksanaan Pendidikan Humanis Religius Di Sd Muhammadiyah Program Khusus Kottabarat Surakarta - Al Islamy, Atalarik Syech; , Minsih, S.Ag, M.Pd (2016)
The aim of this research are (1) Implementation Of Humanism Religious Education In Muhammadiyah Particular Program Elementary School Kottabarat Surakarta. (2) Teacher and headmaster role in humanism religious course. (3) education outcome humanism religious for the student. Methods of collecting data in this study are observation, interview, and documentation. This research was a qualitative description research. It is analyze a phenomenon in a condition by take some conclution as a analyzis result.. Results of the research showed that, (1) The implementation refer to 2013 curriculum, and humanism religious character education include with, the combination of 2013 curriculum with syariah curriculum. The teacher in learning process not only give explaination but also teacher give freedom to the student. So the student must have a responsibility for theirself. The teacher as fasilitator. The way of the student comprehention be inspiration for the teacher. (2)Teacher role try to running teaching and learning that will bring the student to positive character and improve the learning to show and to get student interest to maximize the potential of the student. Headmaster role are guide and give the real example in humanism religious character, controlling, accommodate the different cases and then research appropriate formula to solve the problem. (3) Outcome of humanism religious education are since the student in Muhammadiyah Particular Program Elementary School Kottabarat Surakarta, the student has teach and accustomed behaviour when eating and drinking they must sit down. And then student know if the time to enter the class, they make a march and memorize some surah in alqur'an together.